A study of the effects of situational strength on self-efficacy and happiness: comparing individualist and collectivist cultures - Yeo, Young Hyun; Lee, Ju Ho; Lee, Keon-Hyung (Frontiers in Psychology, 2025)
When individual values, attitudes, and behaviors do not align with dominant cultural expectations, organizational societies often employ situational strength to promote behavioral conformity. While this may enhance organizational efficiency by minimizing variability in individual performance, it can also suppress self-expression and elevate stress—particularly for individuals in collectivist cultures who face stronger normative control. Notably, countries such as South Korea and Japan report lower average levels of happiness compared to Germany and Finland, despite comparable levels of economic development. This study investigates the psychological mechanisms underlying this disparity by examining the role of situational strength within cultural contexts. Using survey data from 608 participants across South Korea, Japan, Finland, and Germany, this study explores how perceptions of situational strength influence self-efficacy and happiness across different cultural orientations. The results indicate that situational strength significantly reduces both self-efficacy and happiness, with particularly strong effects in collectivist societies. Moreover, self-efficacy partially mediates the relationship between situational stress and happiness, highlighting its critical psychological function. Individuals in collectivist cultures experience higher levels of situational strength due to greater societal and organizational pressure to conform, whereas those in individualist cultures report higher autonomy, reduced stress, and greater psychological well-being. These findings advance situational strength theory by demonstrating that its effects on psychological outcomes are not culturally neutral. Rather, they are shaped by sociocultural environments that modulate the experience of conformity pressure. This study contributes to cross-cultural psychology by clarifying how cultural values and institutional norms interact to influence emotional and motivational outcomes.